R. Buckminster Fuller : world man - López, Daniel (López Pérez); Fuller, R. Buckminster (Richard Buckminster), 1895-1983 (Kassler Lectures., 2014)
"Buckminster Fuller (1895-1983) was one of the most innovative and influential thinkers of the twentieth century. Best known as the inventor of the geodesic dome, Fuller sought out long-term, technology-led solutions to the world's most pressing social and environmental problems. His prodigious creative output-from visionary architectural works and experimental structures to expressive drawings and poetic musings-foreshadowed today's green design and prefab housing movements. R.Buckminster Fuller: World Man documents his never-before-published 1966 Kassler lecture at Princeton University School of Architecture. Delivered at the height of his career (Fuller had appeared on the cover of Time magazine in 1964), he used the lecture to reflect on and synthesize his most significant concepts. In addition to a faithful facsimile of the lecture's typewritten transcript, the book includes an introductory essay on Fuller's work, a glossary of key terms and phrases, and an interview with Robert Geddes, the dean responsible for bringing Fuller to teach and lecture at the school"--